Case Report: Anti-MOG Antibody Seroconversion Accompanied by Dimethyl Fumarate Treatment - Takahashi, Keita; Takeuchi, Hideyuki; Fukai, Ryoko; Nakamura, Haruko; Morihara, Keisuke; Higashiyama, Yuichi; Takahashi, Toshiyuki; Doi, Hiroshi; Tanaka, Fumiaki (Frontiers in Immunology, 2021)
Here we report three cases of anti-myelin oligodendrocyte glycoprotein (MOG) antibody–associated disease (MOGAD) mimicking multiple sclerosis in which seropositivity for anti-MOG antibodies occurred during disease-modifying drug dimethyl fumarate (DMF) treatment. These patients developed relapses with anti-MOG antibody seroconversion after switching from fingolimod or steroid pulse therapy to DMF, which was associated with peripheral lymphocyte recovery. MOGAD is considered a humoral immune disease, and DMF reportedly enhances Th2-skewed humoral immune activity. Therefore, we suggest that DMF, but not fingolimod, may exacerbate humoral immune imbalance and enhance autoantibody production, leading to aggravation of MOGAD.